A financial conditions index for the United States - Kimberly Beaton; René Lalonde; Corinne Luu (Bank of Canada, 2009)
The financial crisis of 200709 has highlighted the importance of developments in financial conditions for real economic activity. The authors estimate the effect of current and past shocks to financial variables on U.S. GDP growth by constructing two growthbased financial conditions indexes (FCIs) that measure the contribution to quarterly (annualized) GDP growth from financial conditions. One FCI is constructed using a structural vector-error correction model and the other is constructed using a large-scale macroeconomic model. The authors' results suggest that financial factors subtracted around 5 percentage points from quarterly annualized real GDP growth in the United States in 2008Q4 and 2009Q1 and should subtract another 5 percentage points from growth in 2009Q2. Moreover, to assess the effect of financial shocks in terms of policy interest rate equivalent units, the authors convert the effect of financial developments on growth into the number of basis points by which the federal funds rate has been tightened. The authors show that the tightening of financial conditions since mid-2007 is equivalent to about 300 basis points of tightening in terms of the federal funds rate. Thus, the aggressive monetary easing undertaken by the Federal Reserve over the financial crisis has not been sufficient to offset the tightening of financial conditions. Finally, in a key contribution to the literature, the authors assess the relationship between financial shocks and real activity in the context of the zero lower bound. They find that the effect of the tightening of financial conditions on GDP growth in the current crisis may have been amplified by as much as 40 per cent due to the fact that policy interest rates reached the zero lower bound.
Keywords: E32; E44; E47; E51; 330; Business fluctuations and cycles; Monetary conditions index; Monetary and financial indicators; Recent economic and financial developments; Finanzmarktkrise; Wirtschaftslage; Finanzmarkt; Wirtschaftsindikator; Index; USA